Students Metacognitive Strategies in Solving Mathematics Problems in Distance Learning: A Phenomenological Study - Presto, Adaiah; Menorca, Eugene L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The COVID-19 pandemic has transformed the educational terrain from face-to-face to distance learning. In the Philippines, the Department of Education implemented different distance learning modalities such as modular distance learning, online distance learning, TV/radio-based instruction, and blended distance learning to continue education delivery. Consequently, this study explored senior high school students' experiences using metacognitive strategies to solve pre-calculus problems in distance learning through a phenomenological approach to qualitative research. Using purposive sampling, the researchers selected ten senior high school students from Marinduque and Palawan. They conducted two sets of online interviews via Google Meet to elicit students' experiences, views, and opinions regarding their metacognitive strategies in solving problems in pre-calculus. During the first set, all participants were involved, while they chose only three to proceed to the second set of interviews. They crafted the open-ended questions they utilized in the online interviews according to the research questions. The recorded interviews were transcribed and analyzed through thematic analysis. The results revealed that (1) students' metacognitive strategies for solving problems in pre-calculus include planning, monitoring, and evaluating the solution and final answer. Also, (2) students perceived their metacognitive strategies as practical tools to overcome difficulties in solving pre-calculus problems in distance learning. Further, (3) students recognized their metacognitive strategies in solving problems in pre-calculus as applicable in making decisions in real-life and pursuing lifelong learning.